Roles of simulation model on production of high performance nanocarbon polymer biocomposites - Khairul Anwar, Mohamad Said; Md Rezaur, Rahman (Elsevier Ltd., 2024)
A nanocarbon polymer biocomposite is a material that consists of a polymer matrix that is reinforced with nanocarbon particles. Nanocarbon particles can include materials such as carbon nanotubes, graphene, and carbon black. The polymer matrix provides the bulk of the material’s mechanical and structural properties, while the nanocarbon particles provide additional strength, stiffness, and conductivity. The combination of the polymer and nanocarbon particles can result in a biocomposite material with unique properties that make it suitable for a wide range of applications, including biomedical, electronic, and environmental fields.